The challenges and Prospects of Digital Broadcast Regulation In Nigeria - Ngozi , Olimma Benedette; A. Nzan-Ayang , Michael (MultiTech Publisher, 2023)
The paper meticulously examines the challenges and profound impact of the broadcasting system in Nigeria, conducting a comprehensive analysis of various broadcasting bodies. Employing a survey research method, the study embraces a sample size of 150, effectively representing the study's population. Out of the 150 questionnaires distributed, an impressive 93.3% response rate was achieved, with 140 questionnaires returned. The study underscores that major regulatory approaches, including licensing, sanctioning, arbitrating, and monitoring, play a pivotal role. The findings highlight the crucial role of regulation as a tool wielded by society to scrutinize media content and practices, with the political system shaping the trajectory of these regulations. In conclusion, the paper advocates for a review of the Nigerian Broadcasting Code, emphasizing the imperative of an independent regulatory body. Such a move is seen as essential for fostering pluralism and nurturing healthy competition within the industry.